2020
DOI: 10.3389/fimmu.2019.02923
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Dampens HLA-II Expression on Macrophages via the Up-Regulation of miRNAs Targeting CIITA

Abstract: Macrophages have a major role in infectious and inflammatory diseases, and the available data suggest that Helicobacter pylori persistence can be explained in part by the failure of the bacterium to be killed by professional phagocytes. Macrophages are cells ready to kill the engulfed pathogen, through oxygen-dependent and-independent mechanisms; however, their killing potential can be further augmented by the intervention of T helper (Th) cells upon the specific recognition of human leukocyte antigen (HLA)-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 77 publications
2
30
2
Order By: Relevance
“…CD4 + T cells are key players in the adaptive immune response. Following selection and maturation in the thymus, naïve CD4 + T cells migrate to the periphery where they survey for antigens displayed by human leukocyte antigen class II (HLA-II) molecules present on the surface of professional antigen presenting cells (APCs) [ 1 ], such as Dendritic cells (DCs) [ 2 ], B cells [ 3 ], macrophages [ 4 ], CD4 + T cells and airway and intestinal epithelial cells [ 5 ]. HLA-II molecules are composed of an alpha (α) and beta (β) chain ( Figure 1 ), anchored into the cell membrane, that together form the peptide (p) binding groove [ 1 ] ( Figure 1 A,B).…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells are key players in the adaptive immune response. Following selection and maturation in the thymus, naïve CD4 + T cells migrate to the periphery where they survey for antigens displayed by human leukocyte antigen class II (HLA-II) molecules present on the surface of professional antigen presenting cells (APCs) [ 1 ], such as Dendritic cells (DCs) [ 2 ], B cells [ 3 ], macrophages [ 4 ], CD4 + T cells and airway and intestinal epithelial cells [ 5 ]. HLA-II molecules are composed of an alpha (α) and beta (β) chain ( Figure 1 ), anchored into the cell membrane, that together form the peptide (p) binding groove [ 1 ] ( Figure 1 A,B).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other PTMs, such as formylation or palmitoylation (Box 3), can be found on bacterial immunopeptides, and even host cell-derived immunopeptides might display altered modifications during infection [66]. Bacterial infection can also interfere with host cell antigen presentation [80,100,101], and together with PTMs, such immunomodulatory processes should be considered in future immunopeptidomics studies. Finally, even though immunopeptidomics typically requires large amounts of starting material, recent innovations have allowed downscaling to ca.…”
Section: From Identified Antigens To Effective Vaccinesmentioning
confidence: 99%
“…This was dependent on upregulation of miRNAs let‐7f‐5p, let‐7i‐5p, miR‐146b‐5p, and ‐185‐5p. These miRNAs were increased in mucosal biopsies from gastritis patients, suggesting their role in immune evasion 23 . Arnold et al showed that BATF3‐dependent CD103 + DCs are required for induction of gastric Th1 responses to H pylori in mice, and for recruitment of peripherally induced Tregs to the infected mucosa.…”
Section: Immunologymentioning
confidence: 99%